2023
DOI: 10.3390/ijerph20064822
|View full text |Cite
|
Sign up to set email alerts
|

Be Quiet! Effects of Competing Speakers and Individual Characteristics on Listening Comprehension for Primary School Students

Abstract: Students learn in noisy classrooms, where the main sources of noise are their own voices. In this sound environment, students are not equally at risk from background noise interference during lessons, due to the moderation effect of the individual characteristics on the listening conditions. This study investigates the effect of the number of competing speakers on listening comprehension and whether this is modulated by selective attention skills, working memory, and noise sensitivity. Seventy-one primary scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…For instance, for university students in open-plan environments, it was found that noise sensitivity interacts with the effects of noise on a writing task [15] but not in a collaborative task [16]. Concerning younger students (10-13 years), it was found that higher noise sensitivity was related to increased perceived effort in two-talker noise compared to quiet when performing a sentence comprehension task [17].…”
Section: Effects Of Individual Differencesmentioning
confidence: 99%
“…For instance, for university students in open-plan environments, it was found that noise sensitivity interacts with the effects of noise on a writing task [15] but not in a collaborative task [16]. Concerning younger students (10-13 years), it was found that higher noise sensitivity was related to increased perceived effort in two-talker noise compared to quiet when performing a sentence comprehension task [17].…”
Section: Effects Of Individual Differencesmentioning
confidence: 99%
“…Literature results show that children struggle to understand speech in this type of auditory masking [2] and the specific effect of the noise on every student is further modulated by his/her abilities and subjective perception. This study aimed to explore the relationship between individual factors (noise sensitivity and cognitive abilities) and listening conditions (masking noise composed by two or four talkers) on a sentence comprehension task for primary school students [3].…”
Section: Introductionmentioning
confidence: 99%